A longitudinal observation study assessing changes in indicators of serious injury and violence with alcohol controls in four remote indigenous Australian communities in far north Queensland (2000-2015) - Alan R. Clough; Michelle S. Fitts; Reinhold Muller; Valmae Ypinazar; Stephen Margolis (BMC, 2018)
Abstract Background Legal restrictions on alcohol availability have been used to address violence and injury in the world's remote Indigenous communities. In Australia, alcohol management plans (AMPs) were implemented by the Queensland Government in 2002. This study reports changes in indicators of alcohol-related violence and injury in selected communities. Methods Design and setting: A longitudinal observational study was conducted in four Aboriginal and Torres Strait Islander (Indigenous) communities in Cape York, far north Queensland. All communities are similarly-isolated from population centres where alcohol is available. Data: For 2000 to 2015 inclusive: 1019 Royal Flying Doctor Service aeromedical trauma retrievals; 5641 Queensland Police Service records of unique assault occurrences, including 2936 involving alcohol; and records for 2741 unique assault victims were examined. Data analysis: Rates (per 1000 population) of trauma retrievals, assault occurrences and assault victims (per 1000 population) were compared across three policy phases. Phase 1: 2000 to 2008. Initial restrictions on possession and consumption of alcohol in 'restricted areas' were implemented during 2002-2003. Phase 2: 2009 to 2012. All alcohol was prohibited in three study communities and its legal availability limited in the fourth from 2009. Phase 3: 2013 to 2015. Government reviews of AMP policies in light of legal challenges and community responses characterise this phase. Results Compared with Phase 1, in Phase 2 retrieval rates declined by − 29.4%, assault occurrences by − 34.1% with less than one-third involving alcohol, and assault victims by − 21.1%, reaching historically low levels in 2010-2012. These reductions did not continue consistently. Compared with Phase 1, in Phase 3 retrieval rates, assault occurrence rates and assault victim rates declined by somewhat lesser amounts, − 13.9%, − 15.0% and − 13.4%, respectively. In Phase 3, the proportion of assault occurrences involving alcohol in communities 2, 3 and 4 rose towards pre-2008 levels. Conclusions Early successes of these controversial alcohol restrictions are jeopardised. Indicators of violence and injury appear to be rising once more in some AMP communities. Importantly, rates have not generally exceeded the highest levels seen in Phase 1. Fresh policy action is required with rigorous monitoring to prevent erosion of initial important successes.